Social inversion in the agro from 2010 to 2013 in Colombia (2014)
The investment in the rural sector has been one of the priorities of the Colombian rulers and for several years, they have been working to increase the productivity of rural areas through training to create rural micro enterprises, business partnerships, technical assistance and improving rural housing. Also, investment in infrastructure for the sector, such as irrigation districts, which will allow the incorporation of rural areas to agricultural and livestock production in the country. Subsidies and financial support given allowed cope with natural disasters and increase productivity with quality standards to meet national and international demand for our agricultural products. The challenge of accessing international markets, has focused the social investment on helping the rural sector to be more competitive and at the same level as other nations with whom we have business relationships. The new objectives of social investment are mainly three: first, get a better income for the agricultural sector, increasing the standard of living for rural people. Second, make the agricultural sector to achieve self-sustaining to strength the sector and third, achieving agribusiness friendly to the environment that can be competitive in the international market.